The C-terminus of the long AKAP13 isoform (AKAP-Lbc) is critical for development of compensatory cardiac hypertrophy - Taglieri, Domenico M. (2013)
The objective of this study was to determine the role of A-Kinase Anchoring Protein (AKAP)-Lbc in the development of heart failure, by investigating AKAP-Lbc-protein kinase D1 (PKD1) signaling in vivo in cardiac hypertrophy. Using a gene-trap mouse expressing a truncated version of AKAP-Lbc (due to disruption of the endogenous AKAP-Lbc gene), that abolishes PKD1 interaction with AKAP-Lbc (AKAPLbc-ΔPKD), we studied two mouse models of pathological hypertrophy: i) angiotensin (AT-II) and phenylephrine (PE) infusion and ii) transverse aortic constriction (TAC)-induced pressure overload. Our results indicate that AKAP-Lbc-ΔPKD mice exhibit an accelerated progression to cardiac dysfunction in response to AT-II/PE treatment and TAC. AKAP-Lbc-ΔPKD mice display attenuated compensatory cardiac hypertrophy, increased collagen deposition and apoptosis, compared to wild-type (WT) control littermates. Mechanistically, reduced levels of PKD1 activation are observed in AKAP-Lbc-ΔPKD mice compared to WT mice, resulting in diminished phosphorylation of histone deacetylase 5 (HDAC5) and decreased hypertrophic gene expression. This is consistent with a reduced compensatory hypertrophy phenotype leading to progression of heart failure in AKAP-Lbc-ΔPKD mice. Overall, our data demonstrates a critical in vivo role for AKAP-Lbc-PKD1 signaling in the development of compensatory hypertrophy to enhance cardiac performance in response to TAC-induced pressure overload and neurohumoral stimulation by AT-II/PE treatment.